Next-Generation Sequencing and the CRISPR-Cas Nexus: A Molecular Plant Virology Perspective - Shahid, Muhammad Shafiq; Sattar, Muhammad Naeem; Iqbal, Zafar; Raza, Amir; Al-Sadi, Abdullah M. (Frontiers in Microbiology, 2021)
Next-generation sequencing (NGS) and contemporary CRISPR-Cas technologies have revolutionized all the fields of life sciences and plant virology is not an exception. Both these technilofies offer an unparalleled platform to sequencing and deciphering of viral metagenomes promptly Over the past couple of decades, NGS technologies have improved enormously and have impacted the field of plant virology by prompt sequencing, unbiased and hypothesis-free testing and deciphering viral metagenomes. NGS has enabled the detection of plant viruses that had remained undetectable by conventional approaches, such as quarantine and archeological plant samples, and has helped to track the evolutionary footprints of viral pathogens. The CRISPR-Cas based genome editing (GE) and detection techniques have funneled the development of effective virus resistance approaches. Different versions of CRISPR-Cas have been employed successfully to confer resistance against diverse plant viruses by directly targeting the virus genome or indirectly editing certain host susceptibility factors. Applications of CRISPR-Cas systems include targeted insertion and/or deletion, site-directed mutagenesis, induction/expression/repression of the gene(s), epigenome re-modeling and SNPs detection. The CRISPR-Cas toolbox has been equipped with precision GE tools to engineer the target genome with and without double-stranded breaks or donor templates. This technique also enabled the generation of transgene-free genetically engineered plants, DNA repair, base substitution, prime editing, detection of small molecules, and biosensing in plant virology. The utilities, advantages, applications, bottlenecks of NGS and CRISPR-Cas in plant virology are discussed in this review.